Strategic Innovation and Organizational Sustainability in The Context of Vision 2030 In Saudi Arabia: An Empirical Study - Alawiya Allui; Zainab Rawshdeh (Communications of International Proceedings, 2023)
Contemporary studies are now documenting that strategic innovation is crucial for increased organizational sustainability, however, few studies have been done on the effect of strategic innovation practices and organizational sustainability in the framework of fundamental changes in government development plans or economic diversity. A quantitative, exploratory study design and analysis was carried out through a survey of 350 plus Saudi employees to explore and study the correlation of strategic innovation practices on organizational sustainability, during the implementation of the Kingdom of Saudi Vision 2030. Findings of this study indicate that strategic innovation is notably being practiced in Saudi during the 2030 vision. The results also ascertained that strategic innovation practices tested in this study are found to be positively related to organizational sustainability during this phase. The research importantly adds to the organizational sustainability and strategic innovation extant literature by clarifying their relationship in an emerging economy during a government structural plan change. This paper offers a first comprehensive and exhaustive review on the link of strategic innovation and organizational sustainability frameworks in an emerging economy. Also builds as research on progress, empirical study on the synergy between strategic innovative practices and organizational sustainability during an economic diversification process in an emerging economy.